Tourism and Sustainable Development: Its Impact on Energy, Economy, and CO₂ Emissions - Aplugi, Belantika; Kusumawardani, Deni (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2025)
Objective: This study investigates the effects of tourism on energy consumption, economic growth, and CO₂ emissions using annual data from 2002 to 2022. The main objective is to understand both the short- and long-term relationships between tourism and key economic–environmental dimensions, providing an empirical foundation for sustainable development strategies. Design/Methods/Approach: Secondary data were obtained from the World Development Indicators (WDI). The Autoregressive Distributed Lag (ARDL) model was employed to examine both short- and long-run dynamics among tourism, energy use, economic growth, and CO₂ emissions. The ARDL framework was chosen for its ability to capture temporal adjustment processes and interdependencies across the variables of interest. Findings:The results indicate that, in the short term, tourism significantly increases energy consumption and stimulates economic growth, while its effect on CO₂ emissions is statistically insignificant. In the long run, higher tourist expenditures are associated with lower energy use, reflecting improved energy efficiency within the tourism sector. Conversely, tourism receipts negatively influence economic growth over time, suggesting the presence of economic leakage. Moreover, no significant long-term linkage is found between tourism and CO₂ emissions. Originality/Value: This study contributes by quantifying the multidimensional impacts of tourism on both economic and environmental outcomes within a developing-country context. By employing the ARDL model, it advances the literature on tourism sustainability, offering empirically grounded insights relevant to policy formulation for green growth. Practical/Policy implication: The findings emphasize the need for sustainable tourism policies to mitigate environmental impacts while maintaining economic benefits. Policymakers should prioritize improving energy efficiency within the tourism sector, investing in renewable energy initiatives, and promoting eco-friendly tourism practices. These actions can help balance growth and sustainability, supporting long-term green development goals.